Voltage distribution indices method to analyse the performance of various structures of stray current collectors in direct current transit lines - Ebrahim Zare Juybari; Reza Keypour; Mohsen Niasati (IET Electrical Systems in Transportation)
Abstract The stray current produced by a direct current (DC) transit system leads to the corrosion of rails and metallic structures buried under and around the metro line. One practical approach to diminish current injection into buried structures is to implement stray current collectors underneath the rail. An analytical method is proposed herein using voltage distribution indices (VDIs) to calculate the voltage and current collection level of each collector located under the rail soil, and the solutions are validated by comparing with modelling results. The proposed method helps to achieve the voltage of different points under the ground and the current reaching the collectors using a circuit model, without facing the limitations of practical methods, as a supplementary study for experimental tests. Moreover, the effect of different arrangements of collectors under running rails is modelled. The analytical method is deployed considering two objectives, that is stray current collection by the conductors and a reduction in the installation cost of the conductors. Various arrangements of stray current collectors are compared and evaluated. Using integral and matrix equations, current density and potential at different points under the soil are calculated and the obtained results are compared with European (EN) standards.